1. SURGICAL OUTCOMES OF ABDOMINAL AORTIC ANEURYSM REPAIR VIA THE RETROPERITONEAL APPROACH (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the clinical and anatomical characteristics of patients undergoing retroperitoneal surgical repair for abdominal aortic aneurysms and to evaluate the surgical outcomes of this approach.Method: A retrospective study was conducted on 26 patients with abdominal aortic aneurysm who underwent retroperitoneal surgery at the University Medical Center Ho Chi Minh city from January 2015 to March 2023. Data on patient characteristics, aneurysm features, surgical techniques, and postoperative outcomes were collected and analyzed.Results: The mean patient age was 69.96 ± 5.46 years, with 76.92% being male. Hypertension (80.77%) and coronary artery disease (50.0%) were the most common comorbidities. All aneurysms were fusiform, with a mean diameter of 5.7 ± 1.2 cm. Short and angulated necks accounted for 53.85% of cases. The mean operative time was 229.8 ± 68.1 minutes, and the mean aortic clamping time was 39.9 ± 23.1 minutes. Postoperative complications included acute kidney injury (30.77%), respiratory complications (23.08%), and bleeding (19.23%). The mean hospital stay was 8.5 ± 3.8 days.Conclusions: Retroperitoneal surgical repair for abdominal aortic aneurysm is a viable option for patients with complex anatomical characteristics, particularly those with short and angulated aneurysm necks. This approach reduces gastrointestinal and respiratory complications compared to the transperitoneal approach while maintaining effective vascular access.
Keywords: Retroperitoneal approach; open aortic repair; abdominal aortic aneurysm; surgical outcomes